The Study of Histopathological Changes in Some of Intermediate Hosts Infected With Cystic Echinococcosis - Jasim Hansh, Wesam (University of Thi-Qar Journal of Science, 2019)
The present study aimed to investigate the histopathological changes in liver and lung of sheep, cattle and buffaloes, spleen of cattle and lung of human infected with cystic echinococcosis (Hydatidosis). The infected organs with hydatid cysts were collected from abattoir of Nassiriyah municipality in Thi-Qar province, southern of Iraq and preserved immediately in 10% formalin solution. The gross examination noticed that liver and lung more affected organs with infection of cystic echinococcosis, also harden area was observed around the hydatid cyst and all these cysts were unilocular. The present study showed that the defensive response of hosts represented by formation of massive fibrous layer which surrounded the hydatid cysts in liver, lung and spleen of sheep, cattle and buffaloes.  The fibrosis surrounded the hydatid cyst in lung of human was noticed in this study, also the blood vessels in lung were affected by complications of hydatid cyst. The infiltration of inflammatory cells against expanding cysts was observed in liver of sheep and cattle infected with hydatid cysts. The calcification associated with fibrosis in liver of cattle and buffaloes infected with hydatid cysts was noticed while did not demonstrate in liver of sheep. The degeneration of hepatocytes and enlargement of bile duct was recorded in infected cattle.The histopathological changes in lungs of infected hosts represented by the dilatation of pulmonary alveoli in lung of sheep and cattle, also the cystic echinococcosis is affected on the bronchiole by proliferation of bronchial epithelium in cattle.